Analysis of Pan-Cancer Revealed the Immunological and Prognostic Potential of CBX3 in Human Tumors - Xu, Haitao; Jiang, Caihong; Chen, Dangui; Wu, Youzhi; Lu, Jia; Zhong, Long; Yao, Fusheng (Frontiers in Medicine, 2022)
Chromobox protein homolog 3 (CBX3) has been recognized as a member of the heterochromatin protein 1 family and participate in transcriptional activation or inhibition, cell differentiation and growth. Despite more and more evidence shows that CBX3 has a critical function in the development of some tumors, no systematic extensive analysis of CBX3 has been reported. Thus, we intended to examine the prognostic significance of CBX3 in 33 tumors and investigate its potential immune function. We employed several bioinformatics methods to explore the potential carcinogenic impact of CBX3 premised on the data sets collected from tumor genome maps, human protein maps, cBioPortal, and genotype tissue expression. The approaches include assessing the link between CBX3 and prognosis of different tumors, immune cell infiltration, micro-satellite instability (MSI), DNA methylation, and tumor mutational burden (TMB). The outcomes illustrated that CBX3 was increasingly expressed in 29 tumors. Moreover, CBX3 exhibited a negative correlation with the prognosis of many tumors. The expression of CBX3 was linked to MSI in 12 tumors and TMB in 16 tumors. In 24 tumors, the expression of CBX3 was linked to DNA methylation. Moreover, the CBX3 expression exhibited a negative relationship with the infiltration level of the majority of immune cells, but showed a positive link to T gamma delta cells, central memory T cells, and T helper cells, especially when invading breast carcinoma, thymic carcinoma, colon carcinoma, cutaneous melanoma, endometrial carcinoma, and lung squamous carcinoma. Our research indicates that CBX3 might be used as a prognostic indicator for different malignant tumors due to its function in tumor genesis as well as tumor immunity.